Evaluation of antioxidant effects of neem based constituent azadirachtin-A in rat spermatozoa (Journal of Laboratory Animal Science, 2021)
Technical azadirachtin, a major component of neem, has low acute/subchronic toxicity and non-mutagenic/teratogenic in  mammalian species along with minimal disruption to the ecosystem. The present in vitro study aims to address the potential  evaluation of azadirachtin-A, a tetranortritarpinoid of neem seed kernel, on the antioxidant system of rat spermatozoa to  promote oxidative stress in a dose-dependent manner. To assess the effect of the azadirachtin-A on activities of superoxide  dismutase (SOD), catalase, Glutathione reductase (GR), Glutathione peroxidase (GPx), α-Glucosidase, production of  Hydrogen peroxide (H2O2) and level of lipid peroxidation (LPO) in rat spermatozoa, increasing quantities 0.5 mM, 1  mM, 1.5 mM and 2.0 mM per ml of the azadirachtin-A was added to the cultured medium prior to the addition of cauda  epididymal spermatozoa. The spermatozoa were observed at 6th h post-culture and the expressions of enzyme activities  and production of H2O2, level of LPO were recorded. The activities of antioxidant enzymes decreased significantly while  the levels of H2O2 generation and LPO increased significantly in azadirachtin-A treated spermatozoa in a dose dependent  manner when expressed in terms of milligram protein and milligram DNA. The activity of α- glucosidase, a negative  control against antioxidant enzymes, did not show any significant change at any of the doses. The results suggest that  graded doses of azadirachtin-A elicits depletion of antioxidant defense system in sperm, indicating azadirachtin-A induced  oxidative stress in the epididymal sperm of rats.
Keywords: Azadirachtin-A; Antioxidant enzymes; Oxidative stress; Lipid peroxidation; Cauda epididymal spermatozoa and Rat